Skepticism versus Cosmopolitanism: An Analysis of Perspectives of Robert Dahl and David Held about Sense of Democracy in the Context of Globalization - Pereira, Alexsandro Eugenio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
The purpose of this article is to compare two analytical perspectives that have interpreted the democratization of the international organizations (IOs) in the years 1990 and 2000. The first of this perspectives is supported by authors such as Robert Dahl and Philippe Schmitter who consider improbable to realize the democracy in the space outside the national States. They are 'skeptical', according to the term employed by Dahl to refer to their perspective. On the other hand, David Held sustained a more optimistic interpretation by advocating that the nature of contemporary democracy suffered changes as result of the economic globalization process. For this reason, Held considered possible the democratization of IOs as well as the development of a ‘cosmopolitan citizenship’, located above the limits of the States. To develop the counterpoint between this two perspectives, this article will carry out a literature review of the production of the two authors and will be divided into two main sections. The first one will examine the prospect 'skeptical' of Robert Dahl regarding the possibility of democratization of international organizations. The second section examines the cosmopolitan perspective from David Held. In concluding remarks, the article identifies the elements of reflection generated by two perspectives concerning the sense of democracy in the context of globalization.